THE ROMANIAN ORTHODOX CHURCH IN THE LATE 1940S AND 1950S, ACCORDING TO THE CIA ARCHIVES - BOICU, Dragoș (Studia Universitatis Babeș-Bolyai Theologia Orthodoxa, 2021)
The history of the Romanian Orthodox Church during the communist regime is still far from being known and the historical circumstances are not yet fully understood. In addition to numerous historical sources that can shed light on this rather vast subject, an important resource proves to be the CIA archive. Recently declassified documents reflect a new set of information and describe circumstances that allow for a more nuanced interpretation of the position of Patriarch Justinian Marina in the 1940s and 1950s. This paper aims to explore the Information Reports and Staff notes prepared by the CIA analysts during this period.